The Development of an Air Suction Precision Seed-Metering Device for Rice Plot Breeding - Wei Qin; Yuwu Li; Cheng Qian; Zhuorong Fan; Daoqing Yan; Guo Zou; Siqian Liu; Zaiman Wang; Ying Zang; Minghua Zhang (Agronomy, 2025)
To address the lack of specialized seeding equipment and low manual seeding efficiency in rice plot breeding, this study developed an air suction precision seed-metering device for rice plot breeding, featuring automatic seed-switching and seed-clearing functions controlled by an STM32 microcontroller. Firstly, based on morphological analysis and MATLAB image processing, an active contour method was used to construct a suction hole model. Secondly, to meet the non-contaminated switching requirements between rice varieties, an electrically controlled seed-switching and seed-clearing mechanism was developed based on QR code-based precise recognition and positioning. Using 10 rice varieties as experimental materials, performance tests were conducted. The results showed that the seed-switching mechanism had single and cumulative errors under 0.4°, and the seed-clearing rate reached 100% with an average clearing time below 0.88 s. At a rotational speed of 20 r·min−1 and negative pressure of 3200 Pa, seed-filling performance was optimal for all rice varieties. Among them, the rice variety Nayou 6388 exhibited the best seed-filling performance, with a 0.8% missing seed rate, 97.6% single and double seed rate, and 1.6% multiple seed rate. In double-row coordinated tests, each seed-metering device independently completed seed switching and maintained synchronized operation, meeting agronomic requirements for accurate seed switching/clearing and precision seed filling in rice plot breeding.